Using Communicative Language Teaching (CLT) to improve speaking skills in a1-level 8th graders - Rivera Rivera, Adriana Salomé; Acosta Ortega , María José; Letamendi Lazo , Carmen Andrea; Bonilla Tenesaca , Josué Reinaldo (Arandu UTIC, 2025)
This study evaluated the impact of implementing Communicative Language Teaching (CLT) strategies on the development of English-speaking skills among eighth-grade students at the A1 level. A mixed-methods approach with an explanatory sequential design was used, combining quantitative oral assessments conducted before and after the CLT program implementation with qualitative data obtained through student surveys. Forty students from a public basic education school in the city of Guayaquil participated, engaging for five weeks in communicative activities such as role-plays, collaborative pair work, and listening comprehension exercises. Quantitative results showed significant improvements in students’ fluency, pronunciation, and coherence in conversations. Additionally, qualitative data demonstrated an increase in student motivation and participation. Despite some difficulties, the results show that this communicative methodology is effective and can be applied in similar environments.